When the equation a – bx = cx + d is solved for x, the result is x = StartFraction a minus d Over b plus c EndFraction..

Use the general solution to solve 5 – 6x = 8x + 17.

1 answer

First, we need to rearrange the equation to the form a - bx = cx + d:

a = 5
b = 6
c = -8
d = -17

Now we can use the general solution x = (a - d) / (b + c) to solve for x:

x = (5 - 17) / (6 + (-8))
x = (-12) / (-2)
x = 6

Therefore, the solution to the equation 5 - 6x = 8x + 17 is x = 6.
Similar Questions
  1. A student solved the following equation using the following steps:2(2x+2)=4(x+4) 4x+4=4x+4 4=4 Infinitely many solutions (2
    1. answers icon 1 answer
  2. A student solved the following equation using the following steps:2(2x + 2) = 4(x + 4) 4x + 4 = 4x + 4 4 = 4 Infinite solutions
    1. answers icon 1 answer
  3. 5. A student solved the following equation using the following steps:2(2x+2)=4(x+4) 4x+4=4x+4 4=4 Infinitely many solutions (2
    1. answers icon 29 answers
  4. A student solved the following equation using the following steps:4(2-3x) = x - 2(2x+1) 8 - 3x = x - 4x = 2 8 - 3x = -3x - 2
    1. answers icon 1 answer
more similar questions